The biological activities of new polyamine derivatives as potential therapeutic agents. (1st April 2003) - Kong Thoo Lin, P.; Dance, A.M.; Bestwick, C.; Milne, L.
Abstract : A number of polyamine derivatives have demonstrated potential as therapeutic agents. For example, 1, 12-bisethylspermine and bisnaphthalimide (elinafide) are currently in phase I clinical trials for the treatment of certain cancers. Here, the biological activities of two new groups of polyamine derivative, namely the oxa-polyamines and the bisnaphthalimides, are presented. The most active compounds in the oxa-polyamine and bisnaphthalimido series possessed IC50 values of 2.93 and 1.38 μM, respectively, against MCF7 cells after 48 h of exposure. The structure–relationship activities of each group of compounds are discussed. Bisnaphthalimido compounds are DNA-binding agents. Addition of the bisnaphthalimides PK3, PK4, PK5, PK6 and PK7, at a concentration of 10 μM, to the calf thymus DNA duplex increased the T m of DNA by 11.55±0.56, 14.545±1.59, 6.23±2.45, 12.56±1.84 and 16.45±0.39°C respectively. With the exception of PK5, all compounds bind to DNA by intercalation as judged by effect of compounds on DNA mobility. Ethidium bromide displacement assay showed that all the compounds have significant affinity for calf thymus DNA (the drug concentration required to reduce the fluorescence of initially DNA-bound ethidium bromide by 50%, C50, was 1.21–17.33 μM). The order of DNA-binding strength was PK4 > PK3 > PK7 > PK6 > PK5. In HL-60 promyelocytic leukaemia cells, oxa-polyamine and bisnaphthalimido treatment resulted in a decline in cell proliferation and viability. The assays performed suggested that apoptosis was not the principal cell death mechanism involved in oxa-polyamine cytotoxicity. In contrast, HL-60 cell death induced by the bisnaphthalimido series was characterized by early exposure of phosphatidylserine exclusive from membrane damage, elevated caspase-3 activity, increased DNA instability and, ultimately, DNA fragmentation. Thus the principal cytotoxic members of the bisnaphthalimido series appear to induce apoptosis.